Corrigendum/ Erratum/ Retraction - Timbul (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2013)
Retraction to: Timbul. (2013). Pesantren Sebagai Pusat Peradaban Pendidikan Islam: Pengalaman Indonesia untuk Asia Tenggara. EDUKASI : Jurnal Pendidikan Islam (e-Journal), 1(2), 182–208. Retrieved from https://ejournal.staim-tulungagung.ac.id/index.php/edukasi/article/view/9 This article has been retracted by the publisher based on the following reason: This is based on the original author's report and the author's acknowledgement that by plagiarising the editor that the author committed an ethical violation of the publication. The author acknowledges that he has plagiarised other writers' scripts. Plagiarism articles have been published in EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan (Publisher: the Center for Research and Development of Religious Education [Puslitbang], Agency of Religious Research and Development, Education and Training [Balitbang and Diklat], The Ministry of Religious Affairs, The Republic of Indonesia) Vol. 8 Issue 2 August (2010) (https://jurnaledukasikemenag.org/index.php/edukasi/article/view/104) This article has followed the procedures that apply to journal management. The author has received the review results and has improved the article according to the review result.One of the conditions of submission of a paper for publication in this journal is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere, and also not considered by another journal. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes an extreme view on this matter, and apologies are offered to readers of the journal that this was not detected during the submission process.